Early versus Late Tracheostomy for Intubated Patients in Intensive Care Units - Shkar Nazar Mohammed; Saleh Ahmed Tawfique; Hiwa Asaad Abdulkareem (Advanced Medical Journal)
Background and objectives:Tracheostomy, is an integral component of the management plan for the critically ill patients admitted in the intensive care unit under endotracheal intubation. However, there is controversy regarding the effects of timing of tracheostomy in those patients, which was the purpose of this prospective study.